Keberadaan Mikroba Pemfermentasi pada Minuman Kefir Air Susu Kambing Etawa - Pamericar, Merla; Periadnadi, Periadnadi; Nurmiati, Nurmiati (Metamorfosa: Journal of Biological Sciences, 2018)
Study about existence of fermentation microbe in kefir etawa goat milk had been studied. The objective of this study were to know total of microbe from kefir etawa goat milk. This study used descriptive method and counting population of microbe on in vitro . The variable acid in kefir measuring with pH meter. Result indicated total bacteria in kefir etawa goat milk are sebanyak 98,3 x 10 6 cfu/ml with total yeast 67,8 x 10 5 cfu/ml and pH of kefir 4.57.